1997
DOI: 10.1103/physrevb.55.12552
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic domains in epitaxial ordered FePd(001) thin films with perpendicular magnetic anisotropy

Abstract: Small magnetic domains ͑70 nm͒ have been observed by magnetic force microscopy in ordered FePd thin films grown by molecular-beam epitaxy. The layers exhibit a perpendicular magnetic anisotropy induced by uniaxial L1 0 ͓CuAu͑I͒-type͔ chemical ordering. The magnetization curves show that the easy magnetization axis is perpendicular to the film plane and their interpretation with a micromagnetic model leads to the correct size of the domains.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
110
0
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 197 publications
(119 citation statements)
references
References 13 publications
6
110
0
1
Order By: Relevance
“…Figure 8 shows MFM images of three different samples at zero magnetic field. The images obtained with samples grown at high temperature exhibit alternate dark and bright regions, which is the distinctive feature of samples with perpendicular anisotropy: 32,33 these alternate regions correspond to up and down orientations of the magnetization. However, the sample grown at RT exhibits narrow lines that can be ascribed to magnetic domain walls, 34 meaning that elsewhere the magnetization lies mainly in plane of the film.…”
Section: Magnetic and Magneto-optical Propertiesmentioning
confidence: 94%
“…Figure 8 shows MFM images of three different samples at zero magnetic field. The images obtained with samples grown at high temperature exhibit alternate dark and bright regions, which is the distinctive feature of samples with perpendicular anisotropy: 32,33 these alternate regions correspond to up and down orientations of the magnetization. However, the sample grown at RT exhibits narrow lines that can be ascribed to magnetic domain walls, 34 meaning that elsewhere the magnetization lies mainly in plane of the film.…”
Section: Magnetic and Magneto-optical Propertiesmentioning
confidence: 94%
“…This property can be provided by 3d/4d or 3d/5d ordered alloys in the fcc L1 0 cubic phase presenting alternate planes of magnetic and nonmagnetic atoms, as in CoPt(001), 37,38 FePt(001), 39 and FePd(001) (Ref. 40) compounds, or in 3d/4d or 3d/5d superlattices as in the cases of Co/Pd (Refs. [41][42][43][44] or Co/Pt systems.…”
Section: Introductionmentioning
confidence: 99%
“…The present study shows that the use of recently reported 13 spontaneously aligned magnetic domain morphology (as opposed to maze-like, randomly oriented domains [14][15][16] ) can produce magnetostriction strains at lower switching fields, thereby rendering them magnetically soft while using the same alloy composition and microstructure. Also remarkably, results show that different magnetostriction strain pathways become accessible within the same material depending on the direction of applied field relative to the aligned domains.…”
mentioning
confidence: 79%